Sintegritas Advokat di Indonesia Dalam Pemberian bantuan Hukum secara Cuma-Cuma (Prodeo) - Aina Fazira; Melisa Siregar; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
In carrying out their responsibilities, advocates must be honest, have a strong character, and of course have high intelligence. In addition, advocates must have determination because that is even more important than their skills or vision for the cause. anybody. As a result, Article 28D paragraph (1) of the 1945 Constitution stipulates that